Chapter San Cataldo (Lecce, Italy): The Historical Evolution Of The Coastal Landscape - FERRARI, IVAN (Proceedings e report, 2020)
San Cataldo is located on the Adriatic sea about 10 km east from Lecce (Italy). Since ancient times it was a port and the remains of a Roman pier are visible: the study illustrate the evolution of its coastal landscape from historical origins until today. The port was renovated in medieval times and also between the 19th and 20th centuries with the construction of a lighthouse, a new pier and a tramway with Lecce. During the last century emerged the tourist vocation of San Cataldo with events of overbuilding characterizing the nowadays coastal landscape.